Pencegahan dan Penanggulangan Dampak Covid-19 di Masa Adaptasi Kebiasaan Baru di Dusun Citeureup - Rahayu, Lisda Resti (Journal Pemberdayaan Masyarakat Indonesia, 2023)
The emergence of the corona virus since 2019 has become a big enemy throughout the country because this pandemic does not only have an impact on public health but also affects all aspects of life including in the education and socio-economic fields of the community. So education regarding the understanding of Covid-19 and proper prevention methods directly to the public to increase awareness of oneself to be more aware of the dangers of Covid-19 is deemed necessary for the community, and the socialization of the use of online applications as a learning medium and product marketing is also a good step to maintain the economic stability of the people in the midst of a pandemic. Based on the above problems, through the Real Work Lecture (KKN) activity carried out by the Indonesian Education University (UPI) campus in December 2020 the author tries to take a role in efforts to prevent Covid-19, especially in Dusun Citeureup, Desa Cilayung, Kecamatan Jatinangor, Kabupaten Sumedang with using the method of observation and socialization of education about Covid-19. Based on the dedication that has been done, the results show that the author can add insight in the education and economy of the Citeureup Hamlet community in the midst of the Covid-19 pandemic. In addition, the people of Citeureup Hamlet can adapt well to the environment and new habits in the midst of the Covid-19 pandemic, both from the education and economic sectors.